The great reset : and the war for the world - Jones, Alex, 1974- (Skyhorse Publishing, 2022)
From central bankers, corporate billionaires, and corrupted government officials, global elites have been organizing a historic war on humanity under a trans-humanist, scientific dictatorship. Alex Jones was the first major figure to expose the World Economic Forum's agenda. He has dedicated the last 30 years of his life to studying The Great Reset, conducting tens of thousands of interviews with top-level scientists, politicians, and military officials in order to reverse engineer their secrets and help awaken humanity. The Great Reset And the War for the World chronicles the history of the global elites rise to power and reveals how they've captured the governments of the world and financed The Great Reset to pave the way for The New World Order.